"A True and Patriotic Band!": Welsh Anglican Resistance to a Colonial Victorian Church. Issue 4 (December 2019) - Jones, Matthew C.
Abstract : This essay examines the colonial relationship between the Anglican Church and the British Empire's Welsh subjects across the nineteenth century. Focusing on the small output of a group of exiled Welsh clergymen (known as The Association of Welsh Clergy in the West Riding of the County of York), I consider Welsh Anglican responses to the church's neglect of Wales (exemplified by no Welsh-speaking bishop being assigned to a Welsh diocese between 1727 and 1870, despite the majority of the population not speaking English). The association believed that preaching in a foreign language such as English constituted a perversion from proper church practice and that this both reflected hegemonic attitudes toward indigenous and non-English speaking populations and pushed the Welsh population toward dissent. In response, the association sought to combine church reform with Welsh nationalism by elevating Welsh speakers as the spiritual inheritors of the true and primitive British church. They promulgated their visions in annual reports published between 1852 and 1856 into which they channeled other contemporary voices speaking against tyrannical and "Romish" Anglican Church practices. Through an analysis of post-Reformation Welsh church histories and the reports' usages of such terminology as "alienation, " "Catholicism, " and "patriotism, " I reveal how the Welsh national identity the association fashioned at once operated within and aspired to correct the Anglican Church.